2023
DOI: 10.1177/14771535231158078
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent dimming control and energy consumption monitoring system of tunnel lighting

Abstract: To achieve energy saving and safe driving in a tunnel, this work proposes a tunnel intelligent dimming control and energy consumption monitoring system. Firstly, a dynamic predicted tunnel traffic volume is established to optimize the timeliness of the system tunnel traffic volume. Secondly, a backpropagation neural network-based dimming control model is constructed, in which the luminance outside the tunnel, traffic volume and vehicle speed serve as the input, and the luminance inside the tunnel is the output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Based on research in tunnel lighting that the authors conducted (decentralization research that the Higher Education Department funded), it was found that the lighting in the Pasar Rebo tunnel and the Cibubur tunnel did not meet the lighting standards for both nighttime lighting and daylight lighting [1]. The research conducted to enhance energy efficiency in tunnel lighting applies three methodological approaches: implementing smart lighting technology in the tunnel [2]- [7]; organizing the environment by planting trees and plants at the tunnel entrance [8], [9]; and by replacing HPS lamps with LED lamps. The average lighting during the day is either very excessive, that is, the illumination and luminance exceed the SNI standards and international standards, or much less than standard, especially at mid-day [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on research in tunnel lighting that the authors conducted (decentralization research that the Higher Education Department funded), it was found that the lighting in the Pasar Rebo tunnel and the Cibubur tunnel did not meet the lighting standards for both nighttime lighting and daylight lighting [1]. The research conducted to enhance energy efficiency in tunnel lighting applies three methodological approaches: implementing smart lighting technology in the tunnel [2]- [7]; organizing the environment by planting trees and plants at the tunnel entrance [8], [9]; and by replacing HPS lamps with LED lamps. The average lighting during the day is either very excessive, that is, the illumination and luminance exceed the SNI standards and international standards, or much less than standard, especially at mid-day [10], [11].…”
Section: Introductionmentioning
confidence: 99%